A signature of circulating microRNAs differentiates takotsubo cardiomyopathy from acute myocardial infarction - Jaguszewski, M.; Osipova, J.; Ghadri, J.-R.; Napp, L. C.; Widera, C.; Franke, J.; Fijalkowski, M.; Nowak, R.; Fijalkowska, M.; Volkmann, I.; Katus, H. A.; Wollert, K. C.; et al. (European heart journal, 2014)
Takotsubo cardiomyopathy (TTC) remains a potentially life-threatening disease, which is clinically indistinguishable from acute myocardial infarction (MI). Today, no established biomarkers are available for the early diagnosis of TTC and differentiation from MI. MicroRNAs (miRNAs/miRs) emerge as promising sensitive and specific biomarkers for cardiovascular disease. Thus, we sought to identify circulating miRNAs suitable for diagnosis of acute TTC and for distinguishing TTC from acute MI. After miRNA profiling, eight miRNAs were selected for verification by real-time quantitative reverse transcription polymerase chain reaction in patients with TTC (n = 36), ST-segment elevation acute myocardial infarction (STEMI, n = 27), and healthy controls (n = 28). We quantitatively confirmed up-regulation of miR-16 and miR-26a in patients with TTC compared with healthy subjects (both, P < 0.001), and up-regulation of miR-16, miR-26a, and let-7f compared with STEMI patients (P < 0.0001, P < 0.05, and P < 0.05, respectively). Consistent with previous publications, cardiac specific miR-1 and miR-133a were up-regulated in STEMI patients compared with healthy controls (both, P < 0.0001). Moreover, miR-133a was substantially increased in patients with STEMI compared with TTC (P < 0.05). A unique signature comprising miR-1, miR-16, miR-26a, and miR-133a differentiated TTC from healthy subjects [area under the curve (AUC) 0.835, 95% CI 0.733-0.937, P < 0.0001] and from STEMI patients (AUC 0.881, 95% CI 0.793-0.968, P < 0.0001). This signature yielded a sensitivity of 74.19% and a specificity of 78.57% for TTC vs. healthy subjects, and a sensitivity of 96.77% and a specificity of 70.37% for TTC vs. STEMI patients. Additionally, we noticed a decrease of the endothelin-1 (ET-1)-regulating miRNA-125a-5p in parallel with a robust increase of ET-1 plasma levels in TTC compared with healthy subjects (P < 0.05). The present study for the first time describes a signature of four circulating miRNAs as a robust biomarker to distinguish TTC from STEMI patients. The significant up-regulation of these stress- and depression-related miRNAs suggests a close connection of TTC with neuropsychiatric disorders. Moreover, decreased levels of miRNA125a-5p as well as increased plasma levels of its target ET-1 are in line with the microvascular spasm hypothesis of the TTC pathomechanism.